Comparative Evaluation of Wrinkle Treatments - Ooe, Masahiko; Seki, Taizo; Miura, Tomoe; Takada, Akiyoshi (Aesthetic plastic surgery, 2013)
Background Skin wrinkles are one of the most cosmetically concerning signs of aging for women, and improvements in the visual effect of wrinkles become a matter of concern that has an impact on the quality of life. Although various wrinkle treatments are being tried in the area of aesthetics and noninvasive cosmetic surgery, no guideline on how to treat wrinkles exists to date. This study evaluated the clinical effects of four wrinkle treatment methods [fractional erbium yttrium–aluminum–garnet (YAG) laser treatment, intense pulsed light (IPL) therapy, CD-atRA external application, and nutritional therapy with intake of amino acid supplements]. These four methods were selected as promising candidates in a pilot case study to improve wrinkles by following the consensus guideline (Task Force Committee for Evaluation of Anti-Aging Function, J Jpn Cosmet Sci Soc 31:411–431, 2007) for the evaluation of anti-wrinkle effects issued by the Japan Cosmetic Industry Association. Methods The wrinkle area fraction and skin viscoelasticity were measured by objective evaluation. Furthermore, a satisfaction survey of the subjects was conducted on the basis of subjective evaluations using the visual analog scale (VAS) method and in accordance with the guideline for the evaluation of antiwrinkle effects. Results Fractional erbium YAG laser treatment showed statistically significant improvement in both of the objective evaluations (wrinkle area and skin elasticity). The IPL method showed statistically significant improvement in both of the objective evaluations (wrinkle area and skin elasticity), and it especially demonstrated a more significant difference in skin elasticity. The CD-tretinoin external application method showed statistically significant improvement in both of the objective evaluations (wrinkle area and skin elasticity), and it especially demonstrated a more significant difference in wrinkle area. Nutritional therapy showed statistically significant improvement in wrinkle area, whereas IPL, CD-tretinoin external application, and nutritional therapy demonstrated statistically significant improvement in the degree of wrinkle. As for the subjective assessment of VAS, all four treatments demonstrated equivalent satisfaction. Conclusion All four minimally invasive procedures (fractional erbium YAG treatment, IPL therapy, CD-atRA external application, and intake of amino acid supplements) showed significant improvement of wrinkles. Comparative evaluation of wrinkles using the same criteria is important. The findings clearly showed that an evidence-based approach to wrinkle treatments supported by validation of their effectiveness is required. Level of Evidence IV This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .